IDENTIFIKASI UPAYA INOVATIF PADA SUPPLY CHAIN PT. MULTI BINTANG INDONESIA TBK - Utami, Titah; Wahyono, Seno Aji (Ma Chung Press, 2025)
The supply chain is key to maintaining a company's competitive advantage amidst modern industrial competition. This makes innovation important to be carried out so that supply chain performance is maintained and the company grows. Each component in the supply chain is closely related, supports each other and needs each other, so innovation efforts must be applied evenly. This study examines the innovation efforts that have been carried out by PT. Multi Bintang Indonesia Tbk in its supply chain. This study is a literature review related to sources. Several aspects reviewed include location, global supply chain management, the role of operational managers, organizational structure and work environment, new product design and innovation in the context of operations, processes, and sustainability. Based on the identification of these aspects, it was found that PT. Multi Bintang Indonesia Tbk. has developed and implemented a strong culture of innovation. The company understands the importance of choosing the right location to establish a brewery because of the advantages such as workforce, geographic location, and demand conditions. As a subsidiary of Heineken B.V, PT. Multi Bintang Indonesia Tbk. has access to technology that facilitates end-to-end digitalization of the global supply chain. In terms of the role of operational managers, the company has a universal guide to forming a culture of innovation that is instilled in every employee through webinars, townhall meetings and e-learning. In terms of organizational structure and work environment, the company implements an organic model company structure indicated by the company's openness to socialization activities between employees, a lean organizational structure, and hybrid work implementation. The company also develops new products to adapt to changes in consumer preferences, such as Bintang Radler 0.0%. Cut The Tosh is the company's initiative to innovate in sustainability.